2014
DOI: 10.3390/ijms151019183
|View full text |Cite
|
Sign up to set email alerts
|

Culinary Herbs and Spices: Their Bioactive Properties, the Contribution of Polyphenols and the Challenges in Deducing Their True Health Benefits

Abstract: Herbs and spices have been used for both culinary and medicinal purposes for centuries. Over the last decade, research into their role as contributors of dietary polyphenols, known to possess a number of properties associated with reducing the risk of developing chronic non-communicable diseases, has increased. However, bearing in mind how these foods are consumed, normally in small quantities and in combination with other foods, it is unclear what their true benefit is from a health perspective. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(125 citation statements)
references
References 126 publications
(200 reference statements)
1
120
1
3
Order By: Relevance
“…360.89 mg GAE/100 g fw. Levels of phenolic compounds found in parsley and dill were higher than those reported by Opara and Chohan (2014), ie 89.27 mg GAE/100 g in parsley and 208.18 mg GAE/100 g in dill, but lower than those presented by Shan et al (2005) ie 636 mg GAE/100 g fw in dill and 631 mg/100 g fw in parsley or Číž et al (2010) who reported a total phenolic content of 599.7 mg GAE/100 g in parsley but only 150.4 mg GAE/100 g in dill. Lisiewska et al (2006) between 197 and 331 mg GAE/100 g in dill and showed that the content of polyphenols increased with the increasing height of the plant.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…360.89 mg GAE/100 g fw. Levels of phenolic compounds found in parsley and dill were higher than those reported by Opara and Chohan (2014), ie 89.27 mg GAE/100 g in parsley and 208.18 mg GAE/100 g in dill, but lower than those presented by Shan et al (2005) ie 636 mg GAE/100 g fw in dill and 631 mg/100 g fw in parsley or Číž et al (2010) who reported a total phenolic content of 599.7 mg GAE/100 g in parsley but only 150.4 mg GAE/100 g in dill. Lisiewska et al (2006) between 197 and 331 mg GAE/100 g in dill and showed that the content of polyphenols increased with the increasing height of the plant.…”
Section: Resultscontrasting
confidence: 71%
“…Numerous studies have shown that a high intake of vegetables that are sources of antioxidant compounds is associated with a lower incidence of cardiovascular disease, cancer and other chronic diseases. The relatively low intake levels of culinary herbs and spices do not necessarily mean that they are of little value as their high polyphenol content, and thus ultimately the potential biological impact of this content, cannot be ignored (Opara and Chohan, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…For instance, spices, in which phenolic acids, flavones, and flavonols tend to predominate (58), potently inhibit PL in vitro (7). Alternatively, strawberry polyphenols, which are largely anthocyanins, ellagitannins, and ellagic acid (59), may be more effective at altering carbohydrate metabolism, because they consistently inhibit carbohydrate digestive enzymes (60)(61)(62), and improved the insulin response to white bread in healthy women (11).…”
Section: Discussionmentioning
confidence: 99%
“…The spice is also rich in flavonoid compounds such as quercitin, kaemferol, rhamnetin, and epigenin, as well as bioactive compounds namely phenol caffeic and chorogenic acid [13]. Coriander also contains phenolic compounds by 357.36 mg/100g wet weight [14]. On the other hand, garlic could hamper the microbial growth of Salmonella enteritidis and Staphylococcus aureus [15].…”
Section: Gmp (Good Manufacturing Practice)mentioning
confidence: 99%